Unbroken : an extraordinary true story of courage and survival - Hillenbrand, Laura (London; Fourth Estate, 2012)
The incredible true story of Louis Zamperini.
Keywords: Prisoners of war; Airplane crash survival; Military operations, Aerial--American; United States. Army Air Forces. Bombardment Group, 307th; Zamperini, Louis